Sertipikat Hak Atas Tanah Sebagai Alat Bukti Pemilikan Dalam Rangka Memberikan Kepastian Hukum Atas Tanah - Husen Alting (Fakultas Hukum Universitas Mulawarman, 2010)
The objective of land registration is to obtain law warranty and law protection for the holder of land right. Since UUPA and its regulations are written, the objective is not actually realized. It is evident when it is seen from the technical aspect of land registration. Some procedures and data used by the official may not be well elaborated. The government which is given responsibility for land registration has not certified the land. IN other hand, the land owners with limited economic capability do not have ability to register their land. Many lands are without certification, and as consequence, the law fails to cover the law warranty and law protection to the citizen.